Community Participation-Based Environmental Monitoring in RT 08 RW 04 Malaka Jaya - Amanda Chesaria H; Christian Immanuel P; Rasya Aulia (Journal of Mandalika Social Science, 2026)
Community participation-based environmental monitoring has become an increasingly relevant approach given the limited capacity of government agencies to comprehensively oversee urban residential environmental conditions. This study aims to analyze the effectiveness of community participation-based environmental monitoring at RT 08 RW 04, Malaka Jaya Village, East Jakarta, by simultaneously examining three primary variables: the level of citizen participation, the institutional capacity of RT/RW, and the quality of the residential environment as a response variable. A normative juridical method combined with an empirical approach was employed, utilizing participatory observation, in-depth interviews, and structured questionnaires distributed to household heads within the study area. Data validation was conducted through source triangulation to ensure the credibility and consistency of findings. The results indicate that citizen participation in RT 08 is active, sustained, and grounded in environmental-legal awareness, rather than merely reactive to governmental directives. Institutional capacity proved to be high, underpinned by visionary leadership, innovative community infrastructure, and an extensive cross-sectoral partnership network. Both variables synergistically contributed to measurable improvements in residential environmental quality, evidenced by numerous environmental innovations receiving national and international recognition. This study concludes that the effectiveness of community-based environmental monitoring can only be achieved when citizen participation, institutional capacity, and supportive regulation simultaneously coexist, and recommends the RT 08 model as a national replication reference for urban environmental governance.